Description of Student Discipline Attitudes at SMP Negeri 16 Jambi City - Nadia Natalia Simamora; Wita Ardina Putri; Muhammad Iqbal; Auliya Ramadhanti; Endah Febri Setiya Rini (Lensa: Jurnal Kependidikan Fisika, 2020)
Attitude is a form of one's perception of an object which is depicted through the expression of accepting, rejecting, or ignoring. Discipline attitude is the accuracy in following the rules of the game that has been agreed upon. The purpose of this study was to describe the disciplinary attitudes of student learning towards four indicators in SMP Negeri 16 Jambi City. The research method uses descriptive research. The instrument used was a learning discipline attitude questionnaire. The sample in the study amounted to 69 students. The sampling technique in this study was total sampling. The research instrument used was a learning discipline attitude questionnaire. The questionnaire data were analyzed using descriptive statistics with the help of SPSS 21. The results showed that the learning discipline attitude of dominant students in the category always consisted of 2 indicators, namely obeying and obeying school rules and good attention when learning in class, and also The attitude of student learning discipline is dominant in the frequent category which consists of 2 indicators, namely managing study time at home diligently and regularly studying and doing assignments. Based on the results of the study, it was found that students' learning discipline attitude at SMP Negeri 16 Jambi City in 4 indicators had a positive attitude in the always and often category.